Heat-resistant high-strength insulating material and preparation method thereof

CN123004045APending Publication Date: 2026-10-30广东华声电器实业有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611288382.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]但在高端移动式电缆、户外耐候柔性电缆等特殊应用场景中,尤其是适配H07RN-F标准的柔性线缆,以及需要频繁弯折、扭转、往复拉伸的电气连接线缆使用场合,上述常规绝缘料的综合性能短板凸显

Benefits of technology

1、本申请采用硅烷耦合协同单宁酸原位接枝改性滑石粉,有效解决了传统绝缘料无机填料相容性差、胶料硬度高、高频弯折易开裂的技术问题,通过硅烷偶联剂在滑石粉表面构建共价键连接底层,再借助铁离子催化实现单宁酸均匀原位接枝包覆,在无机粉体表面构筑兼具结合强度与界面活性的有机功能层,从而有效改善无机填料与有机基体的界面相容性,消除了无机填料与橡胶弹性体之间的界面缺陷,规避了传统高填充无机粉体造成的胶料刚性过大、柔性不足的问题,在不降低材料拉伸强度、保留原有力学承载能力的前提下,有效消解无机粉体的刚性堆砌效应,显著降低胶料整体硬度,从根源上实现绝缘料高强度与高柔性的协同匹配。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004045A_ABST
    Figure CN123004045A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of high polymer materials, and particularly discloses a heat-resistant high-strength insulating material and a preparation method thereof. The heat-resistant high-strength insulating material is prepared from raw materials including EPDM, POE elastomer, chlorinated polyethylene, modified talcum powder, heavy calcium powder, flexible heat-resistant phosphonitrile additive, stabilizer, antioxidant, softening agent and crosslinking agent. The modified talcum powder is obtained by in-situ grafting modification of talcum powder with tannic acid. The flexible heat-resistant phosphonitrile additive is obtained by substitution reaction of hexachlorocyclotriphosphazene with sodium long-chain alcohol. Through the synergistic effect of the modified talcum powder and the flexible heat-resistant phosphonitrile additive, the interface compatibility between the inorganic filler and the matrix is improved, and the prepared cable insulating material has good mechanical strength, flexibility and heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of polymer materials technology, and more specifically, it relates to a heat-resistant, high-strength insulating material and its preparation method. Background Technology

[0002] Cable insulation material is a core polymer material used in wire and cable products. It primarily coats the outside of the cable conductor, playing a crucial role in electrical insulation, physical protection, and preventing external environmental corrosion. It directly determines the electrical safety, operational stability, and service life of the cable. With the continuous development of power transmission and electrical equipment, the market's requirements for the comprehensive performance of cable insulation materials are gradually increasing. These materials not only need to possess basic insulation properties but also need to be adaptable to different working conditions, possessing suitable mechanical strength, heat resistance, and processing performance to meet the production and usage needs of various civil and industrial power cables.

[0003] Currently, most commercially available cable insulation materials are made from rubber and polyolefin as base raw materials, combined with conventional additives, and prepared through simple mixing and vulcanization processes. Conventional insulation materials only need to meet the general IE4 insulation standard requirements, specifically the following mechanical and heat resistance parameters: tensile strength ≥ 5 MPa, elongation at break ≥ 200%, heat resistance rating of 70℃, and the hardness of the vulcanized sheet maintained at around 80A. Compared to highly flexible insulation materials, this hardness level offers better rigidity, effectively reducing raw material preparation costs in actual cable production and processing. It also greatly facilitates subsequent refined processing operations such as sheathing, stripping, and terminal crimping, exhibiting strong processing adaptability and wide applicability to the production and use of ordinary fixed-lay cables, as well as most conventional low-voltage cable applications.

[0004] However, in special applications such as high-end mobile cables and outdoor weather-resistant flexible cables, especially in flexible cables compatible with the H07RN-F standard, and in electrical connection cables requiring frequent bending, twisting, and repeated stretching, the shortcomings of conventional insulation materials become apparent. These special operating conditions place extremely high demands on the heat resistance, structural strength, and flexibility of the cable insulation layer. Existing conventional insulation materials with a hardness of 80A are too rigid and lack sufficient flexibility, making them prone to cracking and damage from prolonged and frequent bending. Furthermore, their low heat resistance of 70℃ makes them unsuitable for high-temperature operating environments, and their mechanical strength decreases significantly under high-temperature conditions, making it difficult to maintain a tensile strength standard of ≥5MPa. This easily leads to insulation layer deformation, damage, and insulation failure, failing to meet the long-term stable use requirements of H07RN-F standard flexible cables and cables subjected to high-frequency bending. Therefore, there is an urgent need to develop an insulation material that combines high strength, high heat resistance, and excellent flexibility to address the compatibility deficiencies of existing technologies. Summary of the Invention

[0005] In order to achieve high strength, heat resistance and high flexibility of cable insulation materials, this application provides a heat-resistant high-strength insulation material and its preparation method.

[0006] This application provides a heat-resistant, high-strength insulating material, which adopts the following technical solution: A heat-resistant, high-strength insulating material, comprising the following raw materials in parts by weight: 100-150 parts of EPDM rubber; 100-150 parts of POE elastomer; 40-60 parts of chlorinated polyethylene; 40-60 parts of modified talc; 80-100 parts of heavy calcium carbonate powder; 5-10 parts of flexible heat-resistant phosphazene additive; Stabilizer 8-15 parts; Anti-aging agent 4-6 parts; 20-40 parts of softener; 3-5 parts of crosslinking agent; The modified talc powder is obtained by in-situ grafting modification of talc powder with tannic acid; The flexible heat-resistant phosphazene additive is obtained by a substitution reaction of hexachlorocyclotriphosphazene with long-chain sodium alkoxide.

[0007] This application addresses the common shortcomings of existing general-purpose cable insulation materials, such as low heat resistance, high hardness, easy cracking during high-frequency bending, and severe attenuation of mechanical strength under high-temperature conditions, making them unsuitable for the frequent twisting, dragging, and high-temperature operation conditions of H07RN-F standard mobile flexible cables. It constructs an organic-inorganic hybrid modification system using EPDM rubber, POE elastomer, and chlorinated polyethylene as the composite matrix, combined with tannic acid-grafted modified talc powder and long-chain sodium alkoxide-substituted modified flexible heat-resistant phosphazene additives. This system simultaneously solves the industry pain points of mutual performance constraints in traditional insulation materials at both the microscopic interface structure and macroscopic cross-linking network levels. This solution uses tannic acid-grafted modified talc to replace ordinary talc. Through organic functionalization modification of the powder surface, it effectively improves the interfacial compatibility between inorganic fillers and organic matrix, eliminates interfacial defects between inorganic fillers and rubber elastomers, and avoids the problems of excessive rigidity and insufficient flexibility of rubber compounds caused by traditional high-filler inorganic powders. Without reducing the tensile strength of the material and retaining the original mechanical load-bearing capacity, it effectively eliminates the rigid stacking effect of inorganic powders, significantly reduces the overall hardness of the rubber compound, and achieves a synergistic match between high strength and high flexibility in insulation materials from the root.

[0008] Meanwhile, this application's technical solution introduces a flexible, heat-resistant phosphazene additive prepared by substituting hexachlorocyclotriphosphazene with long-chain sodium alkoxide. Unlike traditional insulating materials that rely solely on the heat resistance of the base rubber matrix, this additive retains the high-bond-energy cyclic phosphazene skeleton, endowing the material with excellent intrinsic heat resistance, effectively breaking through the 70℃ heat resistance limit of traditional insulating materials, and stably adapting to high-temperature operating conditions. The cyclic phosphazene structure can effectively constrain the slippage and relaxation of polymer chains under high-temperature environments, inhibiting matrix structure collapse and mechanical property degradation under high-temperature conditions, solving the core defects of traditional insulating materials such as significant decrease in high-temperature strength and insulation stability failure. Simultaneously, the flexible alkyl segments introduced by the long-chain sodium alkoxide substitution can effectively regulate the hardness of the compound, weakening the rigid stacking effect brought by inorganic fillers, and achieving a synergistic balance between high strength and high flexibility in the material.

[0009] Furthermore, this application constructs a uniform and stable organic-inorganic composite crosslinking network through the organic interface coupling effect of modified talc and the crosslinking synergistic effect of flexible heat-resistant phosphazene additives. The tannic acid active groups on the surface of modified talc can form multi-point interfacial bonds with phosphazene additives and the matrix crosslinking system, enabling stress to be uniformly transmitted and dispersed within the material, significantly improving the overall structural stability of the material. This composite network structure retains the basic mechanical strength and processing adaptability of traditional high-filler insulation systems, while overcoming the shortcomings of traditional systems such as poor heat resistance, insufficient flexibility, and weak resistance to bending fatigue. This allows the insulation material to be stably applied in long-term H07RN-F standard high-end mobile cables, outdoor weather-resistant flexible cables, and various high-frequency bending electrical connection cable scenarios, greatly expanding the application range of general-purpose insulation materials.

[0010] Optionally, the modified talc powder is prepared by the following method: Add talc powder to deionized water and ultrasonically disperse for 10-30 minutes to obtain a talc powder suspension. Add silane coupling agent KH-560 to the suspension and stir for 1-2 hours. Then add tannic acid and ferric chloride hexahydrate and stir for 2-6 hours at 40-70℃. After the reaction is complete, filter and wash, and vacuum dry at 60-80℃ to constant weight. Grind and sieve to obtain modified talc powder.

[0011] By employing the above technical solution, a bilayer modified structure of silane covalent bonding and tannic acid organic coating is constructed by first modifying the surface of talc powder with a silane coupling agent, and then achieving in-situ graft polymerization of tannic acid through the catalytic effect of ferric chloride hexahydrate. The silane coupling agent can build a basic bonding bridge between the inorganic powder and the organic matrix, improving the powder agglomeration problem, while the iron ion catalytic system can significantly improve the grafting efficiency and coating uniformity of tannic acid on the talc powder surface. Compared with single tannic acid modification or single silane modification processes, a dense organic modified layer rich in active functional groups can be formed on the powder surface. This structure completely solves the defects of weak interfacial bonding and easy formation of interfacial voids between unmodified talc powder and the polymer matrix, further strengthening the stress transmission capacity of the inorganic-organic interface, effectively improving the problems of hardness and easy cracking when bending the compound, and providing sufficient active sites for interfacial coupling with flexible phosphazene additives, ensuring the stability of the overall hybrid network.

[0012] Optionally, the solid content of the talc suspension is 10%-15%, and the amount of silane coupling agent KH-560 added is 1%-3% of the mass of talc.

[0013] Optionally, the mass ratio of talc, tannic acid and ferric chloride hexahydrate is 100:(5-15):(2-8).

[0014] By adopting the above technical solution, the ratio of talc, tannic acid and ferric chloride hexahydrate is limited. By adjusting the ratio of the catalytic system and the grafted monomer, the degree of grafting polymerization of tannic acid on the surface of talc and the thickness of the organic coating layer are precisely controlled.

[0015] Optionally, the flexible heat-resistant phosphazene additive is prepared by the following method: Under nitrogen protection, hexachlorocyclotriphosphazene was dissolved in toluene solvent, and then an acid-binding agent was added. Under ice-water bath cooling, a nucleophilic substitution reagent, a mixture of sodium dodecyl alcohol and sodium allyl alcohol, was slowly added dropwise. After the addition was complete, the temperature was raised to 60-100℃, and the reaction was stirred for 12-48 hours. After the reaction was completed, the reaction solution was filtered to remove the generated sodium chloride precipitate. The filtrate was concentrated by rotary evaporation, and the precipitate was precipitated in excess anhydrous ethanol. After filtration and washing, the precipitate was dried under vacuum at 40-60℃ to constant weight to obtain a flexible heat-resistant phosphazene additive.

[0016] By employing the above technical solution, hexachlorocyclotriphosphazene is nucleophilically substituted and modified using a sodium dodecyl alcohol and sodium allyl alcohol complex system. The entire process is protected by an inert gas atmosphere, effectively preventing high-temperature oxidative degradation of the phosphazene groups and ensuring the integrity of the cyclic heat-resistant skeleton structure. Unlike traditional rigid inorganic additives and ordinary flexible additives, the phosphazene additive prepared by this process possesses both a long-chain alkyl flexible structure and allyl active crosslinking sites. The long-chain alkyl group can greatly improve the compatibility between the additive and the rubber matrix, reduce the overall hardness of the rubber compound, and improve its bending resistance. The allyl active sites can participate in the crosslinking reaction of the system, strengthening the crosslinking density and structural stability of the organic-inorganic hybrid network. This fundamentally solves the multiple technical defects of traditional insulation materials, such as low heat resistance, high-temperature strength decay, insufficient flexibility, and easy breakage upon bending.

[0017] Optionally, the acid-binding agent is at least one of anhydrous triethylamine, pyridine, or N,N-dimethylaniline.

[0018] Optionally, the mass ratio of hexachlorocyclotriphosphazene, toluene solvent and acid-binding agent is 1:(5-10):(2-4).

[0019] Optionally, the mass ratio of sodium dodecyl alcohol and sodium allyl alcohol in the nucleophilic substitution reagent is (4-11):1, and the amount of the nucleophilic substitution reagent added is 1.5-2.5 times the mass of hexachlorocyclotriphosphazene.

[0020] By employing the above technical solution and adjusting the ratio of sodium dodecyl alcohol to sodium allyl oxide, the flexibility and crosslinking activity of the phosphazene additive can be precisely balanced. Long-chain sodium dodecyl alcohol primarily provides molecular flexibility, improving the bending performance of the compound, while sodium allyl oxide primarily provides crosslinking activity, ensuring the mechanical strength and structural stability of the material. A reasonable ratio of the two can achieve a precise balance between flexibility and strength, completely resolving the performance contradiction in traditional insulation materials where high strength inevitably leads to stiffness and high flexibility inevitably reduces strength.

[0021] Optionally, the softener is a compound of paraffin oil and naphthenic oil, and the stabilizer is a calcium-zinc stabilizer.

[0022] This application provides a method for preparing a heat-resistant, high-strength insulating material, using the following technical solution: A method for preparing a heat-resistant, high-strength insulating material includes the following steps: S1. Add EPDM rubber, POE elastomer, and chlorinated polyethylene to a mixer for mixing and plasticizing at a temperature of 80-110℃ for 3-8 minutes. Add modified talc, heavy calcium carbonate powder, flexible heat-resistant phosphazene additive, stabilizer, antioxidant, and softener to the mixer and continue mixing at 110-140℃ for 10-20 minutes. Reduce the temperature of the mixer to 90-110℃, add a crosslinking agent, and mix for 3-5 minutes to obtain the mixed rubber compound. S2. The mixed rubber compound is thin-passed and sheeted on a two-roll mill at 140-160℃; the sheeted rubber compound is then subjected to two-stage vulcanization. The first stage vulcanization is carried out at 160-170℃ for 10-15 minutes; the second stage vulcanization is carried out in an oven at 180-200℃ for 4-8 hours to obtain a heat-resistant high-strength insulating material.

[0023] By adopting the above technical solution, the segmented mixing method of first plasticizing the rubber matrix, then adding powder and functional additives step by step, and finally adding crosslinking agents at low temperature effectively avoids the problems of premature crosslinking at high temperatures, additive degradation, and powder agglomeration. This ensures that the modified talc powder and flexible heat-resistant phosphazene additives are uniformly dispersed in the matrix, resulting in the uniform formation of the organic-inorganic hybrid crosslinking network. Precise vulcanization temperature and time parameters ensure sufficient crosslinking of the system without over-vulcanization, forming a structurally stable, moderately flexible, and heat-resistant composite crosslinking system. This fully releases the technical advantages of the modified powder and functional phosphazene additives in this application, ultimately producing an insulating material that combines high strength, high heat resistance, high flexibility, and excellent processability.

[0024] In summary, this application has the following beneficial effects: 1. This application employs silane coupling synergistic in-situ grafting modification of talc powder with tannic acid, effectively solving the technical problems of poor compatibility of inorganic fillers, high hardness of rubber compounds, and easy cracking during high-frequency bending in traditional insulating materials. A covalent bond is constructed on the surface of talc powder using a silane coupling agent to connect the underlying layer. Then, iron ion catalysis is used to achieve uniform in-situ grafting and coating of tannic acid, constructing an organic functional layer on the surface of the inorganic powder that combines bonding strength and interfacial activity. This effectively improves the interfacial compatibility between the inorganic filler and the organic matrix, eliminates interfacial defects between the inorganic filler and the rubber elastomer, and avoids the problems of excessive rigidity and insufficient flexibility in rubber compounds caused by traditional high-filler inorganic powders. Without reducing the tensile strength of the material and retaining its original mechanical load-bearing capacity, it effectively eliminates the rigid stacking effect of inorganic powders, significantly reducing the overall hardness of the rubber compound, and fundamentally achieving a synergistic match between high strength and high flexibility in insulating materials.

[0025] 2. This application introduces long-chain sodium alkoxide to replace the modified flexible heat-resistant phosphazene additive. The flexible heat-resistant phosphazene additive retains the rigid skeleton of the high-bond-energy cyclic phosphazene, giving the material excellent intrinsic heat resistance and stability. It can effectively constrain the movement and relaxation of polymer chain segments at high temperatures, and inhibit high-temperature structural collapse and mechanical decay. At the same time, the long-chain alkyl flexible segments and allyl active crosslinking sites introduced into the molecular structure can simultaneously improve the compatibility between the additive and the matrix and participate in the crosslinking of the system, effectively balancing the rigidity and flexibility of the material. This overcomes the contradiction that traditional insulation materials cannot simultaneously achieve both heat resistance and flexibility, and significantly improves the heat resistance and flexibility of the insulation material.

[0026] 3. This application utilizes the organic-inorganic hybrid synergistic combination of modified talc powder and flexible heat-resistant phosphazene additives, along with a segmented and controllable mixing and vulcanization process, to construct a structurally stable composite cross-linked network, achieving an integrated and synergistic improvement in the high strength, heat resistance, and high flexibility of the insulation material. Modification of a single matrix or optimization of a single filler is insufficient to simultaneously address multiple performance shortcomings of traditional insulation materials. This application leverages the abundant active functional groups on the surface of modified talc powder and the active sites of the phosphazene additives to form multi-point interfacial coupling, enabling the inorganic reinforcing phase and the organic elastic matrix to form a tightly integrated overall network structure, achieving uniform stress transmission and high structural stability. Ultimately, this allows the insulation material to retain excellent processing performance while simultaneously possessing high strength, high heat resistance, and excellent bending flexibility. Attached Figure Description

[0027] Figure 1 The infrared spectrum of the flexible heat-resistant phosphazene additive prepared in Example 4 of this application. Detailed Implementation

[0028] The present application will be further described in detail below with reference to the embodiments.

[0029] Preparation example of modified talc Preparation Example 1 Modified talc powder was prepared using the following method: 9 kg of deionized water and 1 kg of talc were mixed and ultrasonically dispersed for 10 min to obtain a talc suspension with a solid content of 10%. 10 g of silane coupling agent KH-560 was added to the suspension and the mixture was stirred at room temperature for 1 h. Then, 50 g of tannic acid and 20 g of ferric chloride hexahydrate were added, the temperature was raised to 40 °C, and the mixture was stirred at a constant temperature for 2 h. After the reaction was completed, the mixture was filtered, washed repeatedly with deionized water, dried under vacuum at 60 °C to constant weight, and ground through a 200-mesh sieve to obtain modified talc.

[0030] Preparation Example 2 Modified talc powder was prepared using the following method: 8.8 kg of deionized water and 1.2 kg of talc were mixed and ultrasonically dispersed for 20 min to obtain a talc suspension with a solid content of 12%. 24 g of silane coupling agent KH-560 was added to the suspension and the mixture was stirred at room temperature for 1.5 h. Then, 120 g of tannic acid and 60 g of ferric chloride hexahydrate were added, and the mixture was heated to 55 °C and stirred at a constant temperature for 4 h. After the reaction was completed, the mixture was filtered, washed repeatedly with deionized water, dried under vacuum at 70 °C to constant weight, and ground through a 200-mesh sieve to obtain modified talc.

[0031] Preparation Example 3 Modified talc powder was prepared using the following method: Mix 8.5 kg of deionized water with 1.5 kg of talc powder and ultrasonically disperse for 30 min to obtain a talc powder suspension with a solid content of 15%. Add 45 g of silane coupling agent KH-560 to the suspension and stir at room temperature for 2 h. Then add 225 g of tannic acid and 120 g of ferric chloride hexahydrate, heat to 70 °C, and stir at a constant temperature for 6 h. After the reaction is complete, filter, wash repeatedly with deionized water, vacuum dry at 70 °C to constant weight, grind through a 200 mesh sieve to obtain modified talc powder.

[0032] Preparation example of flexible heat-resistant phosphazene additive Preparation Example 4 The flexible heat-resistant phosphazene additive is prepared by the following method: Under nitrogen protection, 1 kg of hexachlorocyclotriphosphazene was dissolved in 5 kg of toluene solvent, and 2 kg of anhydrous triethylamine was added as an acid-binding agent. 1.5 kg of nucleophilic substitution reagent (a mixture of 1.2 kg of sodium dodecyl alcohol and 0.3 kg of sodium allyl alcohol) was slowly added dropwise under ice-water bath cooling, with the addition time controlled at 1 h. After the addition was completed, the temperature was raised to 60 °C, and the reaction was stirred at a constant temperature for 48 h. After the reaction was completed, the sodium chloride precipitate was removed by filtration, the filtrate was concentrated by rotary evaporation, excess anhydrous ethanol was added to precipitate the product, the product was filtered, washed three times with anhydrous ethanol, and dried under vacuum at 40 °C to constant weight to obtain a flexible heat-resistant phosphazene additive.

[0033] Preparation Example 5 The flexible heat-resistant phosphazene additive is prepared by the following method: Under nitrogen protection, 1 kg of hexachlorocyclotriphosphazene was dissolved in 7.5 kg of toluene solvent, and 3 kg of pyridine was added as an acid-binding agent. 2 kg of nucleophilic substitution reagent (a mixture of 1.75 kg of sodium dodecyl alcohol and 0.25 kg of sodium allyl alcohol) was slowly added dropwise under ice-water bath cooling, with the addition time controlled at 1 h. After the addition was completed, the temperature was raised to 80 °C, and the reaction was stirred at a constant temperature for 30 h. After the reaction was completed, the sodium chloride precipitate was removed by filtration, the filtrate was concentrated by rotary evaporation, excess anhydrous ethanol was added to precipitate the product, the product was filtered, washed three times with anhydrous ethanol, and dried under vacuum at 40 °C to constant weight to obtain a flexible heat-resistant phosphazene additive.

[0034] Preparation Example 6 The flexible heat-resistant phosphazene additive is prepared by the following method: Under nitrogen protection, 1 kg of hexachlorocyclotriphosphazene was dissolved in 10 kg of toluene solvent, and 4 kg of N,N-dimethylaniline was added as an acid-binding agent. 2.5 kg of nucleophilic substitution reagent (a mixture of 2.29 kg of sodium dodecyl alcohol and 0.21 kg of sodium allyl alcohol) was slowly added dropwise under ice-water bath cooling, with the addition time controlled at 1 h. After the addition was completed, the temperature was raised to 100 °C, and the reaction was stirred at a constant temperature for 12 h. After the reaction was completed, the sodium chloride precipitate was removed by filtration, the filtrate was concentrated by rotary evaporation, excess anhydrous ethanol was added to precipitate the product, the product was filtered, washed three times with anhydrous ethanol, and dried under vacuum at 40 °C to constant weight to obtain a flexible heat-resistant phosphazene additive.

[0035] Example Example 1 A heat-resistant high-strength insulating material, the raw material composition and formula of which are shown in Table 1, wherein the particle size of the heavy calcium carbonate powder is 2μm, the modified talc powder is the modified talc powder prepared in Preparation Example 1, the flexible heat-resistant phosphazene additive is the flexible heat-resistant phosphazene additive prepared in Preparation Example 4, the stabilizer is a calcium-zinc stabilizer, the antioxidant is antioxidant RD, the softener is a mixture of paraffin oil and naphthenic oil in a mass ratio of 3:1, and the crosslinking agent is rubber crosslinking agent VP-4.

[0036] A method for preparing a heat-resistant, high-strength insulating material includes the following steps: S1. Add EPDM rubber, POE elastomer, and chlorinated polyethylene to a mixer for mixing and plasticizing at 80°C for 8 minutes. Add modified talc, heavy calcium carbonate powder, flexible heat-resistant phosphazene additive, stabilizer, antioxidant, and softener to the mixer and continue mixing at 110°C for 20 minutes. Reduce the mixer temperature to 90°C, add a crosslinking agent, and mix for 5 minutes to obtain the mixed rubber compound. S2. The mixed rubber compound is thin-passed and sheeted on a two-roll mill at 140℃; the sheeted rubber compound is then subjected to two-stage vulcanization. The first stage vulcanization is carried out at 160℃ for 15 minutes; the second stage vulcanization is carried out in an oven at 180℃ for 8 hours to obtain a heat-resistant high-strength insulating material.

[0037] Example 2 A heat-resistant high-strength insulating material, the raw material composition and formula of which are shown in Table 1, wherein the particle size of the heavy calcium carbonate powder is 2μm, the modified talc powder is the modified talc powder prepared in Preparation Example 2, the flexible heat-resistant phosphazene additive is the flexible heat-resistant phosphazene additive prepared in Preparation Example 5, the stabilizer is a calcium-zinc stabilizer, the antioxidant is antioxidant RD, the softener is a mixture of paraffin oil and naphthenic oil in a mass ratio of 3:1, and the crosslinking agent is rubber crosslinking agent VP-4.

[0038] A method for preparing a heat-resistant, high-strength insulating material includes the following steps: S1. Add EPDM rubber, POE elastomer, and chlorinated polyethylene to a mixer for mixing and plasticizing at 95°C for 5 minutes. Add modified talc, heavy calcium carbonate powder, flexible heat-resistant phosphazene additive, stabilizer, antioxidant, and softener to the mixer and continue mixing at 125°C for 15 minutes. Reduce the mixer temperature to 100°C, add a crosslinking agent, and mix for 4 minutes to obtain the mixed rubber compound. S2. The mixed rubber compound is thin-passed and pressed into sheets on a two-roll mill at 150°C. The pressed rubber compound is then subjected to two-stage vulcanization. The first stage vulcanization is carried out at 165°C for 12 minutes. The second stage vulcanization is carried out in an oven at 190°C for 6 hours to obtain a heat-resistant high-strength insulating material.

[0039] Example 3 A heat-resistant high-strength insulating material, the raw material composition and formula of which are shown in Table 1, wherein the particle size of the heavy calcium carbonate powder is 2μm, the modified talc powder is the modified talc powder prepared in Preparation Example 3, the flexible heat-resistant phosphazene additive is the flexible heat-resistant phosphazene additive prepared in Preparation Example 6, the stabilizer is a calcium-zinc stabilizer, the antioxidant is antioxidant RD, the softener is a mixture of paraffin oil and naphthenic oil in a mass ratio of 3:1, and the crosslinking agent is rubber crosslinking agent VP-4.

[0040] A method for preparing a heat-resistant, high-strength insulating material includes the following steps: S1. Add EPDM rubber, POE elastomer, and chlorinated polyethylene to a mixer for mixing and plasticizing at 110°C for 3 minutes. Add modified talc, heavy calcium carbonate powder, flexible heat-resistant phosphazene additive, stabilizer, antioxidant, and softener to the mixer and continue mixing at 140°C for 10 minutes. Reduce the mixer temperature to 110°C, add a crosslinking agent, and mix for 3 minutes to obtain the mixed rubber compound. S2. The mixed rubber compound is thin-passed and pressed into sheets on a two-roll mill at 160℃. The pressed rubber compound is then subjected to two-stage vulcanization. The first stage vulcanization is carried out at 170℃ for 10 minutes. The second stage vulcanization is carried out in an oven at 200℃ for 4 hours to obtain a heat-resistant high-strength insulating material.

[0041] Table 1. Raw material composition and proportions (kg) of the insulating materials in Examples 1-3

[0042] Example 4 A heat-resistant high-strength insulating material, which differs from Example 2 in that: the modified talc powder in this example is the modified talc powder prepared in Preparation Example 1; and the flexible heat-resistant phosphazene additive is the flexible heat-resistant phosphazene additive prepared in Preparation Example 5.

[0043] Example 5 A heat-resistant high-strength insulating material, which differs from Example 2 in that: the modified talc powder in this example is the modified talc powder prepared in Preparation Example 2; and the flexible heat-resistant phosphazene additive is the flexible heat-resistant phosphazene additive prepared in Preparation Example 4.

[0044] Example 6 A heat-resistant, high-strength insulating material differs from Example 2 in that the softener in this example is a mixture of paraffin oil and naphthenic oil in a 1:1 mass ratio.

[0045] Example 7 A heat-resistant, high-strength insulating material, which differs from Example 2 in that: in this example, the softener is a single type of paraffin oil.

[0046] Comparative Example Comparative Example 1 A heat-resistant, high-strength insulating material, which differs from Example 2 in that: no modified talc powder and flexible heat-resistant phosphazene additives were added in this comparative example, and the difference was made up with EPDM rubber.

[0047] Comparative Example 2 A heat-resistant, high-strength insulating material, which differs from Example 2 in that an equal amount of EPDM rubber is used instead of POE elastomer in this comparative example.

[0048] Comparative Example 3 A heat-resistant, high-strength insulating material, which differs from Example 2 in that: in this comparative example, an equal amount of unmodified talc powder is used instead of modified talc powder.

[0049] Comparative Example 4 A heat-resistant high-strength insulating material, which differs from Example 2 in that: no flexible heat-resistant phosphazene additive was added in this comparative example.

[0050] Comparative Example 5 A heat-resistant, high-strength insulating material, which differs from Example 2 in that the amount of softener added in this comparative example is 10 kg.

[0051] Performance testing The insulating materials prepared in Examples 1-7 and Comparative Examples 1-5 were subjected to performance testing, and the specific results are shown in Table 2.

[0052] Table 2 Experimental Results

[0053] As shown in Table 2, Comparative Example 3, using unmodified ordinary talc, produced an insulating material with a hardness of 78.9A, but only an elongation at break of 312%, and a bending cracking count of 7200 cycles, exhibiting poor flexibility and fatigue resistance. In contrast, the embodiments of this application utilize silane-coupled synergistic tannic acid double-layer modified talc, maintaining the material's high tensile strength (above 9.0 MPa) while keeping the hardness of the compound between 72.1 and 75.2A, effectively mitigating the rigidity defects of inorganic fillers. The organic active layer on the modified talc surface optimizes the interfacial bonding state, eliminating interfacial voids and stress concentration problems, significantly improving the compound's flexibility and bending toughness, effectively addressing the inherent tendency of traditional insulating materials to crack easily during high-frequency bending, and achieving a synergistic balance between high strength and high flexibility.

[0054] Comparative Example 4, without the addition of phosphazene additives, relies solely on the heat resistance of the rubber matrix, resulting in a long-term heat resistance rating of only 72°C. This only meets the requirements for traditional ordinary cable laying and cannot be adapted to high-temperature operating conditions. The flexible heat-resistant phosphazene additive prepared in this application possesses a high-bond-energy cyclic phosphazene skeleton, increasing the heat resistance rating of the insulation materials in all embodiments to over 90°C, significantly exceeding the traditional 70°C heat resistance limit. The cyclic phosphazene structure effectively constrains the slippage and relaxation of polymer chain segments under high-temperature conditions, inhibiting matrix thermal degradation and structural collapse. This eliminates the problem of significant decrease in the mechanical strength and insulation stability failure of insulation materials under high-temperature conditions. Simultaneously, the long-chain alkyl flexible segments of the additive further optimize the flexibility of the rubber compound, forming a complementary performance with modified talc, significantly improving the high-temperature service stability of the material.

[0055] Comparative Example 2, which used pure EPDM rubber to replace POE elastomer, showed a significant decrease in matrix flexibility and toughness, with an elongation at break of only 285% and significantly deteriorated bending performance. This demonstrates that a matrix composed of EPDM rubber, POE elastomer, and chlorinated polyethylene can effectively balance material strength and flexibility. Furthermore, compared to the single paraffin oil softening system in Example 7 and the system in Comparative Example 5 with insufficient softener, the paraffin oil and naphthenic oil blended softening system of this application can fully impregnate the polymer matrix and inorganic fillers, further reducing the hardness of the compound and improving the bending toughness of the material, ensuring that the insulating material possesses both excellent mechanical properties and processing compatibility.

[0056] Comparative Example 1, lacking modified talc and flexible heat-resistant phosphazene additives, lacked a complete composite modified cross-linking structure, resulting in inferior overall material performance. It exhibited high hardness, low strength, and poor heat resistance, failing to meet the requirements of H07RN-F standard mobile cables. In contrast, the preferred embodiment 2 of this application, relying on the interfacial coupling effect of modified talc and the cross-linking enhancement effect of phosphazene additives, constructed a uniform and stable composite cross-linking network. The resulting insulation material possesses low hardness, high strength, high heat resistance, and excellent resistance to bending fatigue, making it suitable for demanding operating conditions such as high-frequency torsion, dragging, and high-temperature operation, greatly expanding the applicable range of cable insulation materials.

[0057] Figure 1 The infrared spectrum of the flexible heat-resistant phosphazene additive obtained in Example 4 is shown. Spectral analysis reveals that at 1250 cm⁻¹... -1 The presence of characteristic absorption peaks of the cyclic P=N skeleton nearby proves that the heat-resistant main skeleton of the phosphazene is completely preserved; 980 cm⁻¹ -1 The presence of a characteristic peak for the POC stretching vibration at 2920 cm⁻¹ confirms the successful substitution of the long-chain sodium alkoxide by the graft. -1 The characteristic peaks of saturated alkyl groups at 1650 cm⁻¹ -1 The presence of the characteristic peak of the allyl C=C double bond indicates that the molecule simultaneously possesses a flexible long-chain alkyl group and an active crosslinking site, proving that the target product, a flexible heat-resistant phosphazene additive, has been successfully prepared.

[0058] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A heat-resistant, high-strength insulating material, characterized in that, The raw materials include the following parts by weight: 100-150 parts of EPDM rubber; 100-150 parts of POE elastomer; 40-60 parts of chlorinated polyethylene; 40-60 parts of modified talc; 80-100 parts of heavy calcium carbonate powder; 5-10 parts of flexible heat-resistant phosphazene additive; Stabilizer 8-15 parts; Anti-aging agent 4-6 parts; 20-40 parts of softener; 3-5 parts of crosslinking agent; The modified talc powder is obtained by in-situ grafting modification of talc powder with tannic acid; The flexible heat-resistant phosphazene additive is obtained by a substitution reaction of hexachlorocyclotriphosphazene with long-chain sodium alkoxide.

2. The heat-resistant high-strength insulating material according to claim 1, characterized in that, The modified talc powder was prepared using the following method: Add talc powder to deionized water and ultrasonically disperse for 10-30 minutes to obtain a talc powder suspension. Add silane coupling agent KH-560 to the suspension and stir for 1-2 hours. Then add tannic acid and ferric chloride hexahydrate and stir for 2-6 hours at 40-70℃. After the reaction is complete, filter and wash, and vacuum dry at 60-80℃ to constant weight. Grind and sieve to obtain modified talc powder.

3. The heat-resistant high-strength insulating material according to claim 2, characterized in that, The solid content of the talc suspension is 10%-15%, and the amount of silane coupling agent KH-560 added is 1%-3% of the mass of talc.

4. The heat-resistant high-strength insulating material according to claim 2, characterized in that, The mass ratio of talc, tannic acid and ferric chloride hexahydrate is 100:(5-15):(2-8).

5. The heat-resistant high-strength insulating material according to claim 1, characterized in that, The flexible heat-resistant phosphazene additive is prepared by the following method: Under nitrogen protection, hexachlorocyclotriphosphazene was dissolved in toluene solvent, and then an acid-binding agent was added. Under ice-water bath cooling, a nucleophilic substitution reagent, a mixture of sodium dodecyl alcohol and sodium allyl alcohol, was slowly added dropwise. After the addition was complete, the temperature was raised to 60-100℃, and the reaction was stirred for 12-48 hours. After the reaction was completed, the reaction solution was filtered to remove the generated sodium chloride precipitate. The filtrate was concentrated by rotary evaporation, and the precipitate was precipitated in excess anhydrous ethanol. After filtration and washing, the precipitate was dried under vacuum at 40-60℃ to constant weight to obtain a flexible heat-resistant phosphazene additive.

6. The heat-resistant high-strength insulating material according to claim 5, characterized in that, The acid-binding agent is at least one of anhydrous triethylamine, pyridine, or N,N-dimethylaniline.

7. The heat-resistant high-strength insulating material according to claim 5, characterized in that, The mass ratio of hexachlorocyclotriphosphazene, toluene solvent and acid binder is 1:(5-10):(2-4).

8. The heat-resistant high-strength insulating material according to claim 5, characterized in that, The mass ratio of sodium dodecyl alcohol and sodium allyl alcohol in the nucleophilic substitution reagent is (4-11):1, and the amount of the nucleophilic substitution reagent added is 1.5-2.5 times the mass of hexachlorocyclotriphosphazene.

9. The heat-resistant high-strength insulating material according to claim 5, characterized in that, The softener is a compound of paraffin oil and naphthenic oil, and the stabilizer is a calcium-zinc stabilizer.

10. A method for preparing a heat-resistant high-strength insulating material according to any one of claims 1-9, characterized in that, Includes the following steps: S1. Add EPDM rubber, POE elastomer, and chlorinated polyethylene to a mixer for mixing and plasticizing at a temperature of 80-110℃ for 3-8 minutes. Add modified talc, heavy calcium carbonate powder, flexible heat-resistant phosphazene additive, stabilizer, antioxidant, and softener to the mixer and continue mixing at 110-140℃ for 10-20 minutes. Reduce the temperature of the mixer to 90-110℃, add a crosslinking agent, and mix for 3-5 minutes to obtain the mixed rubber compound. S2. The mixed rubber compound is thin-passed and pressed into sheets on a two-roll mill at 140-160℃. The pressed rubber compound is then subjected to two-stage vulcanization. The first stage vulcanization is carried out at 160-170℃ for 10-15 minutes. The second stage vulcanization is carried out in an oven at 180-200℃ for 4-8 hours to obtain a heat-resistant high-strength insulating material.